Facile and Sensitive Spectrophotometric Technique for the Determination of Carbofuran in its Formulations, Water and Grain Samples with Substituted Anilines - V. Harikishna; N. V. S. Naidu (E-Journal of Chemistry)
Methods are described for the determination of carbofuran in its formulations, in water and grain samples by the diazotization coupling spectrophotometric technique, using substituted anilines such as 4-bromoaniline, 4-methylaniline and 4-aminobenzaldehyde as the coupling agents. The orange red colour formed with 4-bromoaniline shows maximum absorption at 478 nm, yellow colour obtained with 4-methylaniline have maximum absorption at 465 nm whereas a red colour derivative formed with 4-aminobenzaldehyde shows λmax at 472 nm. The methods could be successfully applied for the determination of carbofuran in its formulations, water and grain samples.